National analysis of the Modified Monash Model, population distribution and a socio‐economic index to inform rural health workforce planning. (20th October 2021) - Versace, Vincent L.; Skinner, Timothy C.; Bourke, Lisa; Harvey, Pam; Barnett, Tony
Abstract: Aims: To describe the population distribution and socio‐economic position of residents across all states and territories of Australia, stratified using the 7 Modified Monash Model classifications. The numerical summary, and the methods described, can be applied by a variety of end users including workforce planners, researchers, policy‐makers and funding bodies for guiding future investment under different scenarios, and aid in evaluating geographically focused programs. Context: The Commonwealth Department of Health is transitioning to the Modified Monash Model to objectively describe geographical access. This change applies to the Rural Health Multidisciplinary Training Program, one of the Australian Government's key policies to address the maldistribution of the rural health workforce. Unlike the previously applied Australian Statistical Geography Standard‐Remoteness Areas, a summary of the population in each Modified Monash Model classification is not available, nor is a socio‐economic overview of the communities within these areas. Approach: Spatial analysis of Australian Bureau of Statistics data (Modified Monash Model, population data and the Index of Relative Socio‐economic Advantage and Disadvantage collected or derived from the 2016 census) at the Statistical Area 1—the smallest unit for the release of census data. Conclusion: Linking the Modified Monash Model, a socio‐economic index and granular population data at the national level highlights the disadvantage of many residents in small rural towns (Modified Monash 5). The Modified Monash Model does not exhibit a continuum of the largest population residing in the most accessible classification and the smallest population residing in the least accessible classification that is seen in the Australian Statistical Geography Standard‐Remoteness Areas. Coupled with policy relevance, the advantage of using the Modified Monash Model as the basis for analysis is that it highlights areas that have both a critical mass of residents and differing levels of socio‐economic advantage and disadvantage. This will help end users to target funding to those regions where there is potential to improve access to services for the greatest number of rural residents.